PENGARUH PEMBELAJARAN JARAK JAUH TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN KEWIRAUSAHAAN KELAS XI TATA BOGA SMK NEGERI 4 KOTA JAMBI - Harahap, Juwita Ramadhani; Kasiono, Kasiono (SJEE (Scientific Journals of Economic Education), 2021)
ABSTRACTThis study aims to determine the effect of distance learning on student learning outcomes in the Entrepreneurship subject class XI Catering at SMK Negeri 4 Jambi City which is contained in the following formulation: (1.) Distance Learning Pictures on Entrepreneurship subjects at SMK Negeri 4 Jambi City . (2.) Overview of learning outcomes for Entrepreneurship Class XI Catering at SMK Negeri 4 Jambi City. (3.) The effect of the application of distance learning on student learning outcomes in the subject of Entrepreneurship Class XI Catering at SMK Negeri 4 Jambi City. In this study, it was considered quite good.This research was conducted using a descriptive survey method with a quantitative approach. Data collection techniques used in this study were observation and questionnaires. A total of 109 respondents were taken through the distribution of questionnaires which were determined as samples in this study.The results of the calculations in this study, for Distance Learning obtained TCR of 71.19% with a good category. With learning outcomes that are above the minimum completeness criteria (KKM) 6.5 as many as 52 students, and below the minimum completeness criteria (KKM) 6.5 as many as 58 students. From the results of this study, there is a fairly good influence on the implementation of Distance Learning in class XI Catering at SMK Negeri 4 Jambi City. The application of distance learning is 1,982.Keywords: Distance Learning and Learning Outcomes